Hubungan Minat Belajar dan Disiplin Belajar dengan Hasil Belajar Materi Makna Tari Siswa Kelas X Di SMKN 7 Bekasi - Aulia Syifahani; Dinny Devi Triana; Kartika Mutiara Sari (Program Studi Pendidikan Tari FBS UNJ, 2023)
This study aims to analyze the relationship between learning interest and learning discipline with students' learning outcomes in cultural arts subject matter dance meaning. The research method used is a quantitative method with a correlational approach. The population in this study was all students of class X SMKN 7 Bekasi with 385 people. The samples in this study were taken using Slovin's formula, with a sample size of 197 people. Data collection is done using the picket technique. Research results show that: 1) There is a positive significant relationship between learning interest and learning material results of dance meaning in x-class students at SMKN 7 Bekasi by 46.2% with (r) 0.462. 2) There is a significant positive relationship between learning discipline and learning material results of dance meaning in x-class students at SMKN 7 Bekasi of 22.8% with (r) 0.228. 3) There is a positive significant relationship between learning interest and learning discipline of dance meaning in x-class students at SMKN 7 Bekasi by 54.8% and (r) 0.548. 4) There is a positive significant relationship between learning interest and learning discipline and learning material results in x-class students at SMKN 7 Bekasi by 30% with (r) 0.300.